Tourism Sector in the Short-Run and Economic Growth in North Sumatra, Indonesia - Simatupang, Parhimpunan; ., .; ., . (International Journal of Engineering and Technology, 2018)
In many developing countries, tourism is used as a main strategy to achieve greater economic performance. Increased income, both directly and as a result of the multiplier effects of tourism revenues, earnings of foreign exchange, new employment opportunities, access to foreign direct investment and economic diversification are the potential economic benefits of tourism. Statistics on international tourist arrivals in Indonesia showed an upward trend over the past few years and reached the highest number in 2014, recording almost 9.44 million arrivals. The province of North Sumatra is well known as a tourist destination, as well as an economic hub and commercial centre.  Indeed, the province was able to attract almost 28% (237,830) of tourist arrivals in 2014, an increase of 4.12 % from 2013. With such a tourist arrivals trend, the tourism sectors has significantly contributed to the economic development of North Sumatera.  This paper examined the role of tourism receipts in the short-run economic growth in North Sumatra through error correction method (ECM) from 1986-2014. Econometrics method were used, such as Augmented Dickey-Fuller (ADF) for unit root test, error correction method (ECM) for short run dynamics, and Granger causality test for causal relationships. The standard Granger causality test reveals that there is a unidirectional short-run Granger causality from tourism receipts to economic growth. This study provides evidence to support a tourism-led growth hypothesis in North Sumatra.